The predecessors’ influence upon the quality of winter wheat grain depending on variety properties - Жемела, Г. П.; Курочка, А. О. (Scientific Progress & Innovations, 2012)
The predecessors’ influence upon the grain quality of different soft winter wheat varieties according to biological properties is examined. The varieties Zemlyachka and Volodarka had high indices of protein content. It is established that pea and annual legume glass were the best predecessors. The varieties Zemlyachka and Volodarka had the best indices of grain quality.